Aesthetic interaction and cultural education in Rejang Asta Dala Dance, Ubud - Gusti Ayu Made Puspawati; Hartono; Malarsih (Indonesian Journal of Educational Development (IJED), 2026)
The Rejang Asta Dala dance, as a sacred dance in Ubud, functions not only within religious rituals but also as a medium of cultural education that transmits symbolic values and cultural meanings within its supporting community. However, contemporary practices indicate a shift in orientation toward technical and visual aspects, potentially reducing philosophical depth and the sacred character of the dance. This study aims to analyze aesthetic interactions in the process of transmitting symbolic values and cultural meanings in the Rejang Asta Dala dance. The research employs a qualitative approach using ethnographic methods, including participatory observation, in-depth interviews, and documentation study. Data analysis is conducted through hermeneutic and semiotic perspectives. The findings reveal that the aesthetic elements of the dance, namely movement, spatial orientation, costume, and music (gamelan), function as a symbolic system that encodes Balinese Hindu cosmology, such as Asta Dala, Dewata Nawa Sanga, and Tri Hita Karana. Cultural education takes place through a hermeneutic cycle involving embodied experience in ritual practice (ngayah), intergenerational reflection, and mediation by the customary community (banjar), thereby shaping reflective and agentic cultural subjects. Despite its effectiveness, the sustainability of this dance's educational function faces challenges from tourism and modernization, necessitating efforts to safeguard the integrity of ritual contexts and the community's role as guardian of meaning.